Carbon aerogels towards new candidates for double negative metamaterials of low density. (April 2018) - Xie, Peitao; Sun, Wei; Liu, Yao; Du, Ai; Zhang, Zidong; Wu, Guangming; Fan, Runhua
Abstract: While metal is commonly used to construct electromagnetic metamaterials, herein carbon aerogel constitutes the first example of application as building blocks for metamaterials of low density. The carbon aerogel is synthesized by the sol-gel polymerization of resorcinol with formaldehyde followed by supercritical fulid drying and carbonization. The resulting nanostructure of carbon aerogel is adjusted by the concentrations of the reactants and catalysts in precursor solutions. Negative permittivity and negative permeability are simultaneously achieved in the low density carbon aerogel. The plasma-like negative permittivity is explained well by the low frequency plasmonic state in carbon networks. Equivalent circuit models and conductivity property indicate that permittivity values have heavy dependence on the framework and micropores of carbon aerogel. Negative permeability is attributed to the high-frequency magnetic response of induced circulating currents. The calculation analysis indicates that permeability values have a linear relation with ( ω ) 0.5, showing a relaxation-type spectra unlike "magnetic plasma" of typical metamaterials. This work offers a novel and potentially powerful route for constructing metamaterials with ultralow density at the nanoscale, and can expand the potential applications of metamaterials especially under extreme conditions. Graphical abstract: Image 1